Optimising Assessment in Project-Based Learning to Improve the Quality of STEM Learning - Vika Puji Cahyani; Achmad Romadin; Erniyani; Fahri Anwar; Mohd Zulfakar Mohd Nawi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Project Based Learning is a pedagogical approach that places students at the centre of learning through the completion of real projects, allowing them to integrate theory and practice effectively. This research aims to analyse how systematic and thorough evaluation or assessment can serve as a benchmark for the effectiveness of Project Based Learning-based curriculum. This research is a combination of bibliometric research and Narrative Literature Review. The natural stages of this research are Determination of Purpose and Topic of Review, Search and Selection of Literature Sources, Organisation of Findings, Analysis and Presentation of Findings. The search was conducted specifically on copus indexed articles in 2020-2024 with the help of Publish or Perish software with the keyword ‘project-based learning evaluation’. Systematic and thorough evaluation or assessment can serve as a benchmark for the effectiveness of project-based learning curriculum. There are several solutions in project-based learning assessment including solutions to the need for assessment tools that are able to capture aspects of the process and results in a balanced manner, difficulty in assessing individual contributions in group projects and variations in the quality of projects produced due to differences in abilities and resources